Analisis Kebijakan Penanganan Pencemaran Limbah Cair di Sungai Kalisari Damen Kota Surabaya - Shelly Regeta Febriani; Ummu Sajidah; Berliana Rizky Saputri; Putri Fiorina Prasasti; Fachrunnisa Rosyada (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Environmental pollution, especially water pollution, is still considered a common problem. For example, the appearance of foam in the Kalisari River, Damen, Surabaya City. Along the surface of the river water, there is a foam that almost resembles snow, continuously decorating the surface with an unpleasant smell. This article focuses on the policy analysis related to the management of liquid waste pollution in the river. By using descriptive research methods through qualitative approaches, supported by data collection using interview techniques. The results of the research showed the minimum knowledge and awareness of the public about the danger of liquid waste pollution to the environment, as well as the lack of full attention from the central government to one of the foam waste phenomena in the Kalisari River, Damen, Surabaya City. From this research, it is expected that the government will have a greater role in providing good handling and carrying out evaluations so that it can be a measure of the success of a policy related to the environment.